Isolation of novel variants of infectious bursal disease virus from different outbreaks in Northeast India. (April 2016) - Morla, Sudhir; Deka, Pankaj; Kumar, Sachin
Abstract: Infectious bursal disease virus (IBDV) is a highly infectious disease of young chicken that predominantly affects the immune system. In the present study, we are reporting first comprehensive study of IBDV outbreaks from the Northeastern part of India. Northeast India shares a porous border with four different countries; and as a rule any outbreak in the neighboring countries substantially affects the poultry population in the adjoining states. Nucleotide sequence analysis of the VP2 gene of the IBDV isolates from the Northeastern part of India suggested the extreme virulent nature of the virus. The virulent marker amino acids (A222, I242, Q253, I256 and S299) in the hypervariable region of the Northeastern isolates were found identical with the reported very virulent strains of IBDV. A unique insertion of I/L294V was recorded in all the isolates of the Northeastern India. The study will be useful in understanding the circulating pathotypes of IBDV in India. Highlights: Infectious bursal disease virus (IBDV) isolates from Northeast India. Genotypic characterization of IBDV isolates. Phylogenetic characterization of IBDV isolates.